Comparative study of Oral Nutritional Supplements vs Intralesional Triamcinolone and Hyaluronidase in Oral Submucous Fibrosis - Reema Goswami; Amar Gangwani; Shweta Bhatnagar; Deepti Singh (International Journal of Medical Research and Review, 2014)
Introduction: Oral submucous fibrosis (OSMF) is a common premalignant condition found in Indian subcontinent caused by chewing arecanut, betel quid and gutkha with tobacco. A standard treatment to manage this condition is not yet available. The various modalities of treatment are nutritional oral antioxidants, intralesional injections, and surgical removal of bands. We compared the efficacy of intraoral administration of vitamin B combined with lycopene with intralesional triamcinolone acetonide combined with hyaluronidase and oral vitamin B complex with lycopene.Methods: 80 patients suffering from OSMF diagnosed clinically were treated in Bundlekhand Medical College Sagar for 4 months. The patients were divided into two groups randomly. Group A patients received oral administration of vitamin B complex, lycopene and topical triamcinolone for 4 months. Group B received weekly intralesional injections of triamcinolone combined with hyaluronidase for 8 weeks along with vitamin B complex, lycopene and topical triamcinolone for 4 months. Treatment outcome was evaluated on the basis of improvement in mouth opening, decrease in burning sensation and healing of ulceration.Result: Group B patients receiving intralesional injections of triamcinolone and hyaluronidase along with nutritional supplements showed improvement in degree of trismus as well as burning sensation and ulceration as compared to Group A receiving only nutritional supplements.Conclusion: Intralesional injection of triamcinolone combined with hyaluronidase with oral antioxidants is more effective in treating the patients with OSMF than antioxidants alone. No side effects were seen in both the groups though some patients complained of pain during administration of injection.